2017
DOI: 10.1371/journal.pone.0185473
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of cyclophosphamide-induced taste loss in mice

Abstract: Many commonly prescribed chemotherapy drugs such as cyclophosphamide (CYP) have adverse side effects including disruptions in taste which can result in loss of appetite, malnutrition, poorer recovery and reduced quality of life. Previous studies in mice found evidence that CYP has a two-phase disturbance in taste behavior: a disturbance immediately following drug administration and a second which emerges several days later. In this study, we examined the processes by which CYP disturbs the taste system by exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 85 publications
6
48
0
2
Order By: Relevance
“…Second, it has been reported that chemotherapy is toxic to taste receptor cell progenitors (Mukherjee et al, 2013;Mukherjee et al, 2017;Jewkes et al, 2018;Delay et al, 2019).…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
See 1 more Smart Citation
“…Second, it has been reported that chemotherapy is toxic to taste receptor cell progenitors (Mukherjee et al, 2013;Mukherjee et al, 2017;Jewkes et al, 2018;Delay et al, 2019).…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
“…It is unclear whether the length-dependence of chemotherapy-induced neurotoxicity in the somatosensory system applies to the chorda tympani, with its tortuous length through the petrous part of the temporal bone; but there is evidence that the pattern of gustotoxicity on the tongue roughly follows the distribution of the chorda tympani, with taste receptor cells on the anterior portion of the tongue potentially worst-affected by cyclophosphamide. After cyclophosphamide is injected into mice, anterior (fungiform) papillae are diminished faster, such that type II (PLCβ2 + ) taste cells tend to die sooner after cyclophosphamide injection if situated more anteriorly on the tongue (see Figure 5) (Mukherjee & Delay, 2011;Mukherjee et al, 2013;Mukherjee et al, 2017). Because the posterior part of the tongue is disproportionately dedicated to bitter taste (e.g., Adler et al, 2000;Matsunami, Montmayeur, & Buck, 2000;Voigt et al, 2012;Feeney & Hayes, 2014), this suggests that bitter taste faculties might be preferentially preserved under chemotherapy.…”
Section: Sparing the Posterior Tonguementioning
confidence: 99%
“…This makes CYP particularly toxic to cells engaged in cell renewal, such as cancerous cells or normal cells with short life spans requiring frequent renewal. Previous research with mice has shown that CYP can disrupt taste functions by increasing taste thresholds and decreasing the ability to discriminate different tastes [1619], killing taste sensory cells within taste buds, and suppressing cell renewal involved in replacement of aging taste sensory cells [16, 19]. Several types of cells are found within a taste bud [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of cell cycling of the proliferating cells is relatively high [31], making these cells especially vulnerable to the effects of CYP. A single dose of 75 mg/kg can kill cells within taste buds and severely depress the rate of cell cycling within the basal layer for several days [16, 19]. When mature cells die and there are inadequate replacement cells, additional disruptions in behavioral taste functions occur [16, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation